2007
DOI: 10.1111/j.1471-4159.2007.05119.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of P2X7 receptors decreases glutamate uptake and glutamine synthetase activity in RBA‐2 astrocytes via distinct mechanisms

Abstract: Glutamate clearance by astrocytes is critical for controlling excitatory neurotransmission and ATP is an important mediator for neuron‐astrocyte interaction. However, the effect of ATP on glutamate clearance has never been examined. Here we report that treatment of RBA‐2 cells, a type‐2‐like astrocyte cell line, with ATP and the P2X7 receptor selective agonist 3′‐O‐(4‐benzoylbenzoyl) adenosine 5′‐triphosphate (BzATP) decreased the Na+‐dependent [3H]glutamate uptake within minutes. Mechanistic studies revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 57 publications
7
29
0
Order By: Relevance
“…However, additional experiments are necessary to better understand this feature. P2X 7 receptor activation is known to promote glutamate release in the hippocampus (Fellin et al 2006;Papp et al 2004;Sperlágh et al 2007) and it was recently described as being able to quickly inhibit [ 3 H] glutamate uptake in RBA-2 cells (Lo et al 2008). In line with these results, we observed a significant increase in P2X 7 expression after 15 min of PA, and its immunocontent returned to control levels 60 min after asphyxia.…”
Section: Discussionsupporting
confidence: 89%
“…However, additional experiments are necessary to better understand this feature. P2X 7 receptor activation is known to promote glutamate release in the hippocampus (Fellin et al 2006;Papp et al 2004;Sperlágh et al 2007) and it was recently described as being able to quickly inhibit [ 3 H] glutamate uptake in RBA-2 cells (Lo et al 2008). In line with these results, we observed a significant increase in P2X 7 expression after 15 min of PA, and its immunocontent returned to control levels 60 min after asphyxia.…”
Section: Discussionsupporting
confidence: 89%
“…In the hippocampus it has been shown that neuronal norepinephrine transporters are regulated by P2X receptors that trigger the release of norepinephrine by causing the inversion of the transporter function (Papp et al 2004). Astrocytes express several purinergic receptors (Abbracchio et al 2009) that modulate glutamate (Lo et al 2008;Zeng et al 2009) and GABA (Cristóvão-Ferreira et al 2011) transporters, but the influence of purinergic receptors in the modulation of norepinephrine transport by astrocytes has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia preconditioning and certain agents, such as ceftriaxone, were reported to protect ischemic injury through upregulating GLT-1 (21). Additionally, the metabolic conversion of glutamate to glutamine by GS could accelerate the extracellular glutamate uptake by reducing the intracellular glutamate concentration, thus playing a protective role following ischemia (22). In the present study, the levels of GLT-1 and GS increased on day 3 in the ischemia group, indicating that an internal potential protective mechanism within the body is functioning.…”
Section: Discussionmentioning
confidence: 99%